An alternative and robust formulation of the fatigue crack growth rate curve for long cracks - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Weiterentwicklung des Exponentialansatzes zur Beschreibung von Rissfortschrittskurven - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta

Simulation-based investigation of the metrological interface structural resolution capability of X-ray computed tomography scanners - Busch, Matthias; Hausotte, Tino (Journal of Sensors and Sensor Systems)
Abstract. The miniaturisation of components leads to new demands on measurement systems. One of these is the resolution. As a volumetric analysis method and method of non-destructive testing, industrial X-ray computed tomography (XCT) has the ability to measure geometrical features and their corresponding dimensions without destroying them and can therefore be used for quality assurance. However, the concept of resolution is not trivial for XCT and has not yet been finally clarified. In particular, the interface structural resolution, the detectability of two surfaces facing each other after surface segmentation, faces a lack of a test specimen, a corresponding measurand and a reliable method. Simulation-based XCT investigations of a method to determine this type of resolution are presented in this article using the geometry of a test specimen that contains several radially arranged holes of the same size. The borehole diameters correspond to the distance between the holes to investigate the resolvability of surfaces and interfaces. The evaluation is based on mean and extreme values of grey value profiles between the individual boreholes of the reconstructed volume. It is shown that the geometrical detectability of the test specimen surface and interface can be extended by a reasonable choice of the threshold value for surface segmentation within a defined interval. With regard to the resolving capability, a distinction is made between assured detectability and possible detectability, as well as the threshold value used when using the ISO50 threshold for surface segmentation and measurement chain completion.
Keywords: Electrical and Electronic Engineering; Instrumentation

Anrisserkennung an geclinchten Proben während einer zyklischen Belastung unter Nutzung eines Scanning Laser Doppler Vibrometers - Brosius, Alexander; Ewenz, Lars; Stephan, Richard; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Ableitung flacher Probengeometrien zur Abbildung mehraxialer Spannungszustände in Clinchverbindungen unter zyklischer Beanspruchung - Ewenz, Lars; Kuczyk, Martin; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Untersuchungen zum Geometrie- und Frequenzeinfluss bei der Ermittlung zyklischer Kennwerte geclinchter Überlappverbindungen - Ewenz, Lars; Kühne, R.; Schöne, S.; Zimmermann, Martina (Tagung Werkstoffprüfung 2022)

Versatile self-piercing riveting with a tumbling superimposed punch - Wituschek, S.; Elbel, L.; Lechner, M. (Materials Research Proceedings)
Abstract. Increasing resource efficiency is a major challenge and affects almost every aspect of social and economic life. The mobility sector in particular is responsible for a large share of primary energy consumption and is increasingly in the focus of public interest. One possibility to adress these challenges is to reduce the vehicle weight by means of lightweight construction technologies such as multi-material systems. These assemblies consist of workpieces with different mechanical and geometrical properties, which poses a major challenge for joining technology. Mechanical joining processes such as semi-tubular self-piercing riveting are often used in the production of these assemblies, but due to their process characteristics, they are rigid and can only react to changing process variables to a limited extent. One way to increase the versatility of self-piercing riveting is to superimpose a tumbling kinematics on the punch. During tumbling, an angular offset of the punch axis to the tool axis is set and the contact area between punch and workpiece is reduced. In this work, investigations were carried out to determine how the tumbling strategy, consisting of the parameters tumbling angle, tumbling onset and tumbling kinematics, affects the material flow of the rivet element. For this purpose, experimental tests are conducted with the typical materials of conventional multi-material systems and the geometric joint formations are determined by means of macrographs.

Comparison of ex- and in-situ investigations of clinched single-lap shear specimens - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Materials Research Proceedings)
Abstract. Force-displacement measurements and macrosections are commonly used methods to validate numerical models of clinching processes. However, these ex-situ methods often lead to springback of elastic deformations and crack-closing after unloading. In contrast, the in-situ computed tomography (CT) can provide three-dimensional images of the clinching point under loading conditions. So far, the quantity of elastic springback that causes measuring deviations between in- and ex-situ measurements is not determined. In this paper, a method is described to quantitatively compare the results of in-situ CT, ex-situ CT and CT scans of cut specimens, which are prepared for macrosectioning, among each other. The method is applied to a single-lap shear test of two clinched aluminum sheets. Here, the test is conducted to specific process steps, then the specimen is CT scanned in-situ (during loading) and ex-situ (after unloading). Subsequently, the specimens are cut for macrosectioning and CT scanned. Finally, the outer contours and the interfaces of cross section images are determined by digital image analysis and the deviations over the clinching point between ex- and in-situ methods are calculated.

In-situ Computed Tomography and Transient Dynamic Analysis of a Single-Lap Shear Test with a Composite-Metal Clinch Point - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Lecture Notes in Production Engineering)

A calibration method for failure modeling in clinching process simulations - Böhnke, Max; Bielak, Christian Roman; Friedlein, Johannes; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)
Abstract. In the numerical simulation of mechanical joining technologies such as clinching, the material modeling of the joining parts is of major importance. This includes modeling the damage and failure behavior of the materials in accordance with varying occurring stress states. This paper presents a calibration method of three different fracture models. The calibration of the models is done by use of experimental data from a modified punch test, tensile test and bulge test in order to map the occurring stress states from clinching processes and to precisely model the resulting failure behavior. Experimental investigations were carried out for an aluminum alloy EN AW-6014 in temper T4 and compared with the simulative results generated in LS-DYNA. The comparison of force-displacement curves and failure initiation shows that the Hosford–Coulomb model predicts the failure behavior for the material used and the tests applied with the best accuracy.

Influence of plastic orthotropy on clinching of sheet metal - Friedlein, Johannes; Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Mergheim, Julia; Steinmann, Paul; Meschut, Gerson (Materials Research Proceedings)

Numerical Investigation of the Coupled Friction Behavior in the Clinching Process Chain - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Lecture Notes in Mechanical Engineering)

Dynamic conformity assessment for joining force monitoring using Bayes filters - Butzhammer, Lorenz; Kappe, Fabian; Meschut, Gerson; Hausotte, Tino (Materials Research Proceedings)
Monitoring force-displacement or force-time curves is a widely used quality control technique in the field of mechanical joining. For online monitoring of self-piercing riveting, envelope curves are often used to define a tolerance zone for the measured setting force. However, the measurement uncertainty is typically not considered and the force curve of a joint can be wrongly rated as non-conform due to measurement errors and noise. In this article, we present a method for dynamical online filtering and uncertainty determination for noisy force curves using two types of Bayesian filters. The methodology is based on a Bayesian probability framework using a priori information for the process curve and sensor noise. To investigate the general feasibility of the method, force measurements with different noise levels are simulated and processed. The conformity is further assessed taking the uncertainty of the filtered signal into account. The results show that the Bayes filter technique is principally able to reduce noise for well-known characteristics of the process curve and sensor noise. Advantages over common filtering techniques, especially for experimental conditions with less known characteristics, are still to be verified. The methodology could be used in future for closed-loop controls to adapt process parameters dynamically.

Combination of versatile self-piercing riveting processes - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Materials Research Proceedings)
Due to economic and ecological framework conditions, a resource-saving utilization of raw materials and energy is becoming increasingly important in particular in the mobility sector. For the reduction of moving masses and the resources consumed, lightweight construction technologies are part of modern production processes in vehicle manufacturing, for example in the form of multi-material systems. Challenging in the manufacture of multi-material systems especially in view of changing supply chains is the variety of materials and geometries that bring conventional joining processes to their limits. Therefore, new processes are required, which can react versatile to process and disturbance variables. A widely used industrial joining process is semi-tubular self-piercing riveting, which is however a rigid process. To increase the versatility, the two newly established processes multi-range self-piercing riveting and tumbling self-piercing riveting are combined and the capabilities for targeted material flow control are united. Therefore, an innovative two-stage process based on the combination is introduced in this paper. The rivet is set with the multi-range self-piercing riveting process with an overlap of the rivet head and then formed by a tumbling process. Further, a specific adaptation of the tumbling strategy is used to investigate the possibility of reducing cracks in the rivet head. Thereby, different tumbling strategies are used and similar geometric joint formations are achieved to compare the results.

Bruchmechanische Untersuchung des Dualphasenstahls HCT590X unter Temperatureinfluss - Weiß, Deborah; Duffe, Tobias; Buczek, Moritz; Kullmer, Gunter; Schramm, Britta

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
AlSi casting alloys combine excellent castability with high strength. Hence, this group of alloys is often used in the automotive sector. The challenge for this application is the brittle character of these alloys which leads to cracks during joint formation when mechanical joining technologies are used. A rise in ductility can be achieved by a considerable increase in the solidification rate which results in grain refinement. High solidification rates can be realized in twin–roll casting (TRC) by water-cooled rolls. Therefore, a hypoeutectic EN AC–AlSi9 (for European Norm - aluminum cast product) is manufactured by the TRC process and analyzed. Subsequently, joining investigations are performed on castings in as-cast and heat-treated condition using the self-piercing riveting process considering the joint formation and the load-bearing capacity. Due to the fine microstructure, the crack initiation can be avoided during joining, while maintaining the joining parameters, especially by specimens in heat treatment conditions. Furthermore, due to the extremely fine microstructure, the load-bearing capacity of the joint can be significantly increased in terms of the maximum load-bearing force and the energy absorbed.
Keywords: Condensed Matter Physics; General Materials Science

Influence of Kinematic Hardening on Clinch Joining of Dual-Phase Steel HCT590X Sheet Metal - Friedlein, Johannes; Mergheim, Julia; Steinmann, Paul (The Minerals, Metals & Materials Series)
Nowadays, clinching is a widely used joining technique, where sheets are joined by pure deformation to create an interlock without the need for auxiliary parts. This leads to advantages such as reduced joining time and manufacturing costs. On the other hand, the joint strength solely relies on directed material deformation, which renders an accurate material modelling essential to reliably predict the joint forming. The formation of the joint locally involves large plastic strains and possibly complex non-proportional loading paths, as typical of many metal forming applications. Consequently, a finite plasticity formulation is utilised incorporating a Chaboche–Rousselier kinematic hardening law to capture the Bauschinger effect. Material parameters are identified from tension–compression tests on miniature spec- imens for the dual-phase steel HCT590X. The resulting material model is implemented in LS-Dyna to study the locally diverse loading paths and give a quantitative statement on the importance of kinematic hardening for clinching. It turns out that the Bauschinger effect mainly affects the springback of the sheets and has a smaller effect on the joint forming itself.
Keywords: Clinching; Material modelling; Kinematic hardening; Parameter identification; Bauschinger effect

Numerical and experimental identification of fatigue crack initiation sites in clinched joints - Ewenz, L.; Bielak, Christian Roman; Otroshi, Mortaza; Bobbert, Mathias; Meschut, Gerson; Zimmermann, M. (Production Engineering)
In this paper, a study based on experimental and numerical simulations is performed to analyze fatigue cracks in clinched joints. An experimental investigation is conducted to determine the failure modes of clinched joints under cyclic loading at different load amplitudes with single-lap shear tests. In addition, numerical FEM simulations of clinching process and subsequent shear loading are performed to support the experimental investigations by analyzing the state of stresses at the location of failure. An attempt is made to explain the location of crack initiation in the experiments using evaluation variables such as contact shear stress and maximum principal stress.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)
Force–displacement measurements and micrograph analyses are commonly used methods to validate numerical models of clinching processes. However, these methods often lead to resetting of elastic deformations and crack- closing after unloading. In contrast, the in situ computed tomography (CT) can provide three-dimensional images of the clinch point under loading conditions. In this paper, the potential of the in situ investigation of a clinching process as validation method is analyzed. For the in situ testing, a tailored test set-up featuring a beryllium cylinder for load-bearing and clinching tools made from ultra-high-strength titanium and Si3N4 are used. In the experiments, the clinching of two aluminum sheets is interrupted at specific process steps in order to perform the CT scans. It is shown that in situ CT visualizes the inner geometry of the joint at high precision and that this method is suitable to validate numerical models.
Keywords: Clinching; Non-destructive testing; Computed tomography; In situ CT

Investigation of the influence of formed, non-rotationally symmetrical pin geometries and their effect on the joint quality of steel and aluminium sheets by direct pin pressing - Römisch, David; Kraus, Martin; Merklein, Marion (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Resource-saving and sustainable production is becoming increasingly important regarding social, political and economic aspects, thus making the use of lightweight-construction technologies a current trend. For this reason, multi-material-systems made of high-strength steel and aluminium as well as metal and fibre-reinforced plastics gain in importance. However, different material properties, e.g. stiffness, thermal expansion coefficients or chemical incompatibilities, are challenging for conventional joining technologies. Joining by cold formed pin structures has shown to have high potential for joining multi-material-systems. These pins can be joined either by direct pin pressing into an unperforated joining partner or by caulking, where the pins are inserted through a pre-punched joining partner and the pin head is upset, resulting in a form-fit joint. Usually, cylindrical pins are used for joining. However, non-rotationally symmetrical pin geometries offer the possibility of introducing a predetermined breaking point or reinforcing a connection in the principal force direction. In this work, cylindrical pins as well as non-rotationally symmetrical pin geometries, such as polygonal and oval pin structures, are cold extruded from the sheet metal plane of an HCT590X+Z dual phase steel and joined in the next step with an EN AW-6014 aluminium using direct pin pressing. Since the formation of an undercut has an crucial influence on the joint strength, the investigations will be focused on the resulting joint geometry. In addition, the effect of different pin heights will be examined to analyse the joint formation at different levels of compression of the pin structures. Finally, the joints are evaluated regarding their joint strength in tensile shear tests and cross tension tests. Here the flow resistance of the geometry used as well as the pin height and thus the strain hardening of the pin base during the extrusion of the pins play a decisive role for the shear strength.
Keywords: Mechanical Engineering; General Materials Science

Joining of CFRT/Steel Hybrid Parts via Direct Pressing of Cold Formed Non-Rotational Symmetric Pin Structures - Popp, Julian; Römisch, David; Merklein, Marion; Drummer, Dietmar (Applied Sciences)
In this study, quasi-unidirectional continuous fiber reinforced thermoplastics (CFRTs) are joined with metal sheets via cold formed cylindrical, elliptical and polygonal pin structures which are directly pressed into the CFRT component after local infrared heating. In comparison to already available studies, the unique novelty is the use of non-rotational symmetric pin structures for the CFRT/metal hybrid joining. Thus, a variation in the fiber orientation in the CFRT component as well as a variation in the non-rotational symmetric pins’ orientation in relation to the sample orientation is conducted. The created samples are consequently mechanically tested via single lap shear experiments in a quasi-static state. Finally, the failure behavior of the single lap shear samples is investigated with the help of microscopic images and detailed photographs. In the single lap shear tests, it could be shown that non-rotational symmetric pin structures lead to an increase in maximum testing forces of up to 74% when compared to cylindrical pins. However, when normalized to the pin foot print related joint strength, only one polygonal pin variation showed increased joint strength in comparison to cylindrical pin structures. The investigation of the failure behavior showed two distinct failure modes. The first failure mode was failure of the CFRT component due to an exceedance of the maximum bearing strength of the pin-hole leading to significant damage in the CFRT component. The second failure mode was pin-deflection due to the applied testing load and a subsequent pin extraction from the CFRT component resulting in significantly less visible damage in the CFRT component. Generally, CFRT failure is more likely with a fiber orientation of 0° in relation to the load direction while pin extraction typically occurs with a fiber orientation of 90°. It is assumed that for future investigations, pin structures with an undercutting shape that creates an interlocking joint could counteract the tendency for pin-extraction and consequently lead to increased maximum joint strengths.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Joining Processes for Fibre-Reinforced Thermoplastics: Phenomena and Characterisation - Troschitz, Juliane; Gröger, Benjamin; Würfel, Veit; Kupfer, Robert; Gude, Maik (Materials)
Thermoplastic composites (TPCs) are predestined for use in lightweight structures, especially for high-volume applications. In many cases, joining is a key factor for the successful application of TPCs in multi-material systems. Many joining processes for this material group are based on warm forming the joining zone. This results in a change of the local material structure characterised by modified fibre paths, as well as varying fibre contents, which significantly influences the load-bearing behaviour. During the forming process, many different phenomena occur simultaneously at different scales. In this paper, the deformation modes and flow mechanisms of TPCs during forming described in the literature are first analysed. Based on this, three different joining processes are investigated: embedding of inserts, moulding of contour joints, and hotclinching. In order to identify the phenomena occurring in each process and to describe the characteristic resulting material structure in the joining zones, micrographs as well as computed tomography (CT) analyses are performed for both individual process stages and final joining zones.

Über die Abgrenzung von Auflösungskonzepten in der industriellen Computertomografie - Binder, Felix; Hausotte, Tino (tm - Technisches Messen)
Unter dem Begriff der Auflösung wird für gewöhnlich das kleinste messbare Merkmal eines Messsystems verstanden. In der dimensionellen Computertomografie hingegen haben sich in den vergangenen Jahren mehrere Auflösungskonzepte etabliert, die aufgrund der fehlenden Normung zueinander im Kontrast stehen. In diesem Beitrag werden die drei häufigsten Konzepte, die Voxelgröße, die Ortsauflösung und die metrologische Strukturauflösung in Kürze vorgestellt. Anschließend wird eine Abgrenzung zwischen den Konzepten getroffen und ein Integration der bestehenden Konzepte in ein gemeinsames Amplituden-Wellenlängen Diagramm diskutiert.
Keywords: Electrical and Electronic Engineering; Instrumentation

Herausforderungen bei computertomografischen Untersuchungen von Fügeverbindungen - Busch, Matthias; Butzhammer, Lorenz; Hausotte, Tino (tm - Technisches Messen)
Die Erkennbarkeit von Rissen und geometrischen Qualitätskennwerten von Fügeverbindungen mittels Computertomografie ist von der Interfacestrukturauflösung abhängig, welche mittels geeigneter Prüfkörper untersucht wird. Die Reduktion von Abbildungsartefakten im Bereich von Bauteilzwischenräumen und -oberflächen verbessert deren dimensionelle Erfassbarkeit.
Keywords: Electrical and Electronic Engineering; Instrumentation

Knowledge and Data-Based Design and Dimensioning of Mechanical Joining Connections - Zirngibl, Christoph; Sauer, Christopher; Schleich, Benjamin; Wartzack, Sandro (Volume 2: 42nd Computers and Information in Engineering Conference (CIE))
Challenges in the development of resource-efficient lightweight designs, such as emission and cost targets in production, lead to an increasing demand for environmentally friendly and fast joining processes. Therefore, cold-forming mechanical joining techniques provide an energy-efficient alternative in comparison to established processes, such as spot welding. However, to ensure a sufficient reliability of the product design, not only the selection of an appropriate manufacturing and joining method, but also the suitable dimensioning and validation of the entire joining process is a crucial step. In this context, thermal processes offer a large number of design principles while mechanical joining methods mainly require extensive experimental tests and the inclusion of expert knowledge. Although few contributions already investigated the data-based analysis of mechanical joints, a system for the requirement- and manufacturing-oriented dimensioning of joining components, such as different profiles and blanks, in combination with the estimation of joint properties is not available yet. Motivated by this lack, this contribution introduces an engineering workbench for the support of design engineers in the early development phases of the knowledge and data-based design of mechanical joining connections using clinching as an example. In this regard, the approach is demonstrated involving a similar material and sheet thickness combination with static loads.

Estimation of Clinch Joint Characteristics Based on Limited Input Data Using Pre-Trained Metamodels - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (AI)
Given strict emission targets and legal requirements, especially in the automotive industry, environmentally friendly and simultaneously versatile applicable production technologies are gaining importance. In this regard, the use of mechanical joining processes, such as clinching, enable assembly sheet metals to achieve strength properties similar to those of established thermal joining technologies. However, to guarantee a high reliability of the generated joint connection, the selection of a best-fitting joining technology as well as the meaningful description of individual joint properties is essential. In the context of clinching, few contributions have to date investigated the metamodel-based estimation and optimization of joint characteristics, such as neck or interlock thickness, by applying machine learning and genetic algorithms. Therefore, several regression models have been trained on varying databases and amounts of input parameters. However, if product engineers can only provide limited data for a new joining task, such as incomplete information on applied joining tool dimensions, previously trained metamodels often reach their limits. This often results in a significant loss of prediction quality and leads to increasing uncertainties and inaccuracies within the metamodel-based design of a clinch joint connection. Motivated by this, the presented contribution investigates different machine learning algorithms regarding their ability to achieve a satisfying estimation accuracy on limited input data applying a statistically based feature selection method. Through this, it is possible to identify which regression models are suitable to predict clinch joint characteristics considering only a minimum set of required input features. Thus, in addition to the opportunity to decrease the training effort as well as the model complexity, the subsequent formulation of design equations can pave the way to a more versatile application and reuse of pretrained metamodels on varying tool configurations for a given clinch joining task.
Keywords: Industrial and Manufacturing Engineering

Characterisation of lateral offsets in clinch points with computed tomography and transient dynamic analysis - Köhler, D.; Sadeghian, B.; Troschitz, J.; Kupfer, R.; Gude, M.; Brosius, A. (Journal of Advanced Joining Processes)
Clinching is a very cost-efficient method for joining two or more sheets made of identical or different materials. However, the current evaluation methods cannot confirm the critical geometrical features of joints such as neck thickness, undercut, and bottom thickness. Furthermore, the effects caused by joining process such as elastic deformation and crack-closure are significant for the joining quality, but often earn insufficient attention. Therefore, computed tomography (CT) and Transient Dynamic Analysis (TDA) as an ultrasonic testing and evaluation procedure are combined to overcome the obstacles mentioned above. In order to have a well-defined and reproducible typical geometrical error in clinching, specimens with a pre-specified lateral offset of the punch with 0.1 mm, 0.2 mm are as well as with no lateral offset are investigated using CT. The specimens are treated with conductive copper varnish in varying intensities to support the two sheets' distinguishability in the CT measurement. The subsequently extracted surfaces from CT-scan data are used to create three-dimensional models for a numerical Transient Dynamic Analysis. Hereby, a harmonic force is applied to one sheet and the transferred energy is determined at the opposite side of the clinch point on the other sheet. The transmitted energy can be used as a quantitative measure for the joining quality. This setup is simulated by means of Finite-Element-Method and the specimens are investigated experimentally using a piezo actuator and a piezo sensor. The novelty of the results presented here is the completely non-destructive investigation of joint specimen by CT of similar materials with a contrast given foil in between the sheets and the subsequent TDA, which can easily detect difference between the specimens by evaluation of the energy dissipation of the joints.

Joining of continuous fiber reinforced thermoplastic/steel hybrid parts via undercutting pin structures and infrared heating - Popp, J.; Drummer, D. (Journal of Advanced Joining Processes)
Continuous fiber reinforced thermoplastics (CFRT)/steel hybrid parts offer promising properties and possibilities, which can exceed the capabilities of both individual materials. In this case, the joining operation presents the main challenge. This paper studies the direct pin pressing where metallic pins with undercutting geometries, protruding from the metal component, are inserted into a locally infrared heated CFRT component. The aim is to investigate the joining process with a focus on the filling of the undercut features with matrix and fibers to create a primarily form-fitting joint. For good mechanical properties of the joint, it is crucial, that the undercutting features are filled and do not lead to significant deconsolidations. The pin structures are manufactured from 42CrMo4 steel on a cnc-lathe and are joined via welding with HCT600+Zn sheet metal. The CFRT samples are manufactured from polypropylene and approximately 45% vol. unidirectional glass fibers. In the scope of this study, different pin geometries are joined with varying process settings and micro sections of the joints are investigated via reflected light microscopy. It could be shown that the undercuts can be completely filled with matrix and fiber material using the described process route. Based on the optical investigations a suitable setting of joining parameters is defined and lap shear as well as cross head samples are manufactured and experimentally tested. It could be seen that independently from the pin geometry the lap shear strength was primarily limited due to shear failure of the pin structures and it is assumed that the base diameter and pin strength predominantly determine the joint strength. Cross head samples failed due to pin extraction. Here, a significant increase of the joint strength with undercutting features could be shown in comparison to cylindrical reference pins.

Effect of the tool geometry on microstructure and geometrical features of clinched aluminum - Ewenz, L.; Kuczyk, M.; Zimmermann, M. (Journal of Advanced Joining Processes)
In addition to brazing and welding processes, mechanical joining processes such as clinching are increasingly being used. Clinch joints offer an advantage over metallurgical joining processes by giving the possibility of joining different material combinations without typical drawbacks. Thereby clinching offers an enormous advantage for lightweight construction. An additional benefit is a great variability in the geometric shapes of the toolsets, which ensure optimum adaptation of the clinching process on variations of the joining elements such as e.g. the sheet thickness. However, the vast variability is also one of the major challenges regarding the prediction of the joint reliability. In the work presented, the effect of different toolset geometries was investigated with a particular focus on the interaction between geometrical features and deformation-induced microstructural changes. Light optical and electron microscopy techniques, as well as micro-hardness measurements, were performed. The results were evaluated and discussed concerning the material's deformation behavior, the change in geometrical shape and the microstructural evolution due to the different tool geometries. The findings point out the main influence factors regarding the mechanical properties in general and the fatigue behavior in particular.

Forming process induced material structure of fibre-reinforced thermoplastics - Experimental and numerical investigation of a bladder-assisted moulding process - Gröger, B.; Würfel, V.; Hornig, A.; Gude, M. (Journal of Advanced Joining Processes)

Investigation of the influence of the tumbling angle on a tumbling self-piercing riveting process - Wituschek, S.; Lechner, M. (Production Engineering)
To achieve the climate objectives, various measures are taken to increase the efficiency of raw materials and energies used. A sector with a large proportion of the global consumption of resources is the mobility sector. To increase the efficiency in this field, large efforts are made to reduce the weight of moving masses. One approach is the use of multi-material systems, which utilises different materials and their specific properties depending on the local requirements. Multi-material systems consist often of materials which differ in strength and density, for example, high-strength steels, aluminium alloys or polymers. Additionally, such a system can utilise different geometries of the components to be joined, characterised for example by varying sheet thicknesses. A central challenge of producing these systems is the joining of the individual components. This requires robust joining processes capable of covering the entire spectrum of possible variants and is feasible for different physical properties of the materials. Since conventional joining processes are rather rigid and have difficulty reacting to changing process and disturbance variables, new joining processes are necessary. With the objective of being able to react versatile to varying parameters, a process combination consisting of a semi-tubular self-piercing riveting process and orbital forming process with adjustable tumbling kinematic is introduced. Due to the process combination of tumbling and self-piercing riveting, mutual influences of the two process components are analysed in regard to material flow and process forces. Further, the investigations show the influence of a varying tumbling angle on the joining process itself and how the characteristic properties undercut, rivet head end position and residual sheet thickness of the joint are affected. The material used for the joining partners is an aluminium alloy EN AW-6014 typical for multi-material systems in the automotive industry and the rivets are from type Rivset C produced by the Böllhoff company.

Analysis of the interactions between joint and component properties during clinching - Steinfelder, C.; Acksteiner, J.; Guilleaume, C.; Brosius, A. (Production Engineering)
Clinching is a joining process that is becoming more and more important in industry due to the increasing use of multi-material designs. Despite the already widespread use of the process, there is still a need for research to understand the mechanisms and design of clinched joints. In contrast to the tool parameters, process and material disturbances have not yet been investigated to a relatively large extent. However, these also have a great influence on the properties and applicability of clinching. The effect of process disturbances on the clinched joint are investigated with numerical and experimental methods. The investigated process variations are the history of the sheets using the pre-hardening of the material, different sheet thicknesses, sheet arrangements and punch strokes. For the consideration of the material history, a specimen geometry for pre-stretching specimens in uniaxial tension is used, from which the pre-stretched secondary specimens are taken. A finite element model is set up for the numerical investigations. Suitable clinching tools are selected. With the simulation, selected process influences can be examined. The effort of the numerical investigations is considerably reduced with the help of a statistical experimental design according to Taguchi. To confirm the simulation results, experimental investigations of the clinch point geometry by using micrographs and the shear strength of the clinched joint are performed. The analysis of the influence of difference disturbance factors on the clinching process demonstrate the importance of the holistic view of the clinching process.

Application of an edge detection algorithm for surface determination in industrial X-ray computed tomography - Busch, M.; Hausotte, T. (Production Engineering)
Surface determination is an essential step of the measurement process in industrial X-ray computed tomography (XCT). The starting point of the surface determination process step is a single grey value threshold within a voxel volume in conventional surface determination methods. However, this value is not always found in the reconstructed volume in the local environment of the surface of the measurement object due to various artefacts, so that none or incorrect surfaces are determined. In order to find surfaces independently of a single grey value, a three-dimensional approach of the initial contour determination based on a Prewitt edge detection algorithm is presented in this work. This method is applied to different test specimens and specimen compositions which, due to their material or material constellation, their geometric properties with regard to surfaces and interfaces as well as their calibrated size and length dimensions, embody relevant properties in the examination of joining connections. It is shown that by using the surface determination method in the measurement process, both a higher metrological structure resolution and interface structure resolution can be achieved. Surface artefacts can be reduced by the application and it is also an approach to improved surface finding for the multi-material components that are challenging for XCT.

Design of clinched joints on the basis of binding mechanisms - Kalich, J.; Füssel, U. (Production Engineering)
The work carried out is based on the thesis properties of clinched joints are determined by the proportions of binding mechanisms form-closure, force-closure and material-closure. To describe the acting binding mechanisms and thus to derive the joint properties, detailed knowledge of the local effect of the individual binding mechanisms is necessary to ensure their targeted adjustment by the joining process. The targeted setting of different proportions of the binding mechanisms is achieved firstly via tool geometry and secondly via surface condition of the joined parts. An introduced form-closure component can be quantified by metallographic cross section with subsequent measurement of the quality-determining parameters such as undercut, penetration depth and neck thickness. To qualify the force-closure component, a torsional load can be applied mechanically at rotationally symmetrical clinch joints. This also allows the influence of different surface conditions on the tribological system to be quantified. Measurement of electrical resistance can reveal the binding mechanisms of force- and material-closure. These investigations are carried out on an aluminum joining part combination of the same type. As a result of these investigations, the clinched joints can be designed according to the load occurring in the later life cycle in the form of an optimum and compromise variant with regard to minimum loads to be transmitted mechanically, electrically with regard to low resistance or manufacturing with minimum energy input.

Observations on additive plasticity in the logarithmic strain space at excessive strains - Friedlein, J.; Mergheim, J.; Steinmann, P. (International Journal of Solids and Structures)
Additive plasticity in the logarithmic strain space is compared to multiplicative plasticity for various loading cases including coaxial and non-coaxial plastic deformations. Even though both finite plasticity approaches are based on total Lagrangian descriptions, the former is popular due to its inherent similarity to the infinitesimal theory and its easy extensibility. However, since its introduction several limitations of additive plasticity in the logarithmic strain space have been discovered. In this study, these problems such as stress rotation and softening are considered, revealing that fundamental differences compared to multiplicative plasticity occur for non-coaxial plastic deformations. We focus in particular on the observed softer response of the additive based approach, which is analysed in depth using three numerical examples including two well-known benchmarks for finite plasticity. By means of these finite element simulations the softer and possibly even localising response of additive plasticity in the logarithmic strain space is confirmed.

Corrosion Phenomena and Fatigue Behavior of Clinched Joints: Numerical and Experimental Investigations - Harzheim, Sven; Ewenz, Lars; Zimmermann, Martina; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Lightweight construction has increasingly become the focus of scientific research in recent years, not least due to the constantly increasing fuel price, which is a key factor in the economic viability of many companies. In this respect, the use of hybrid structures, made of dissimilar materials offers many advantages. However, such hybrid structures often have undesirable side effects. For example, brittle intermetallic phases are formed when aluminum and steel are welded. Clinching as a mechanical joining process does not produce such intermetallic phases since the connection is realized through form and force closure. In this process, a punch passes through two or more sheets and forms them into a permanent joint in a die. In the present work, the corrosion phenomena of an aluminum-steel clinched joint have been investigated by both experiments and numerical simulations in order to explain the superior fatigue behavior of pre-corroded joints. Therefore, the clinched joints have been corroded by a three-week salt-spray test. In addition, the electric potential and the von Mises stress are calculated under the assumption of a static loading. The results of both experiments and numerical simulations can explain the improvement in the fatigue behavior of the corroded specimens. This phenomenon can be attributed to the accumulation of corrosion products in small gaps between the joined metal sheets.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

The Influence of Heat Treatment on the Microstructure, Surface Roughness and Shear Tensile Strength of AISI 304 Clinch Joints - Zeuner, André Till; Ewenz, Lars; Kalich, Jan; Schöne, Sebastian; Füssel, Uwe; Zimmermann, Martina (Metals)
Clinching is the manufacturing process of joining two or more metal sheets under high plastic deformation by form and force closure without thermal support and auxiliary parts. Clinch connections are applicable to difficult-to-join hybrid material combinations, such as steel and aluminum. Therefore, this technology is interesting for the application of AISI 304 components, as this material is widely used as a highly formable sheet material. A characteristic feature of AISI 304 is its metastability, i.e., the face-centered cubic (fcc) γ-austenite can transform into a significantly stronger body-centered cubic (bcc) α’-martensite under plastic deformation. This work investigates the effect of heat treatment—a process that involves the formation of an oxidation layer on the sheet surface—on the forming process during joining and the resulting mechanical properties of clinch joints made from AISI 304. For this purpose, different joints made from non-heat treated and heat-treated sheets were examined using classical metallography and advanced SEM techniques, accompanied by further investigations, such as hardness and feritscope measurements. The shear tensile strength was determined, and the fracture behavior of the samples was investigated. Clear influences of heat-treatment-induced surface roughness on the joint geometry and strength were observed.
Keywords: General Materials Science; Metals and Alloys

Robustness Analysis of Pin Joining - Römisch, David; Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro; Merklein, Marion (Journal of Manufacturing and Materials Processing)
The trend towards lightweight design, driven by increasingly stringent emission targets, poses challenges to conventional joining processes due to the different mechanical properties of the joining partners used to manufacture multi-material systems. For this reason, new versatile joining processes are in demand for joining dissimilar materials. In this regard, pin joining with cold extruded pin structures is a relatively new, two-stage joining process for joining materials such as high-strength steel and aluminium as well as steel and fibre-reinforced plastic to multi-material systems, without the need for auxiliary elements. Due to the novelty of the process, there are currently only a few studies on the robustness of this joining process available. Thus, limited statements on the stability of the joining process considering uncertain process conditions, such as varying material properties or friction values, can be provided. Motivated by this, the presented work investigates the influence of different uncertain process parameters on the pin extrusion as well as on the joining process itself, carrying out a systematic robustness analysis. Therefore, the methodical approach covers the complete process chain of pin joining, including the load-bearing capacity of the joint by means of numerical simulation and data-driven methods. Thereby, a deeper understanding of the pin joining process is generated and the versatility of the novel joining process is increased. Additionally, the provision of manufacturing recommendations for the forming of pin joints leads to a significant decrease in the failure probability caused by ploughing or buckling effects.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Characterisation of Fibre Bundle Deformation Behaviour—Test Rig, Results and Conclusions - Borowski, Andreas; Gröger, Benjamin; Füßel, René; Gude, Maik (Journal of Manufacturing and Materials Processing)
Deformation of continuous fibre reinforced plastics during thermally-assisted forming or joining processes leads to a change of the initial material structure. The load behaviour of composite parts strongly depends on the resultant material structure. The prediction of this material structure is a challenging task and requires a deep knowledge of the material behaviour above melting temperature and the occurring complex forming phenomena. Through this knowledge, the optimisation of manufacturing parameters for a more efficient and reproducible process can be enabled and are in the focus of many investigations. In the present paper, a simplified pultrusion test rig is developed and presented to investigate the deformation behaviour of a thermoplastic semi-finished fiber product in a forming element. Therefore, different process parameters, like forming element temperature, pulling velocity as well as the forming element geometry, are varied. The deformation behaviour in the forming zone of the thermoplastic preimpregnated continuous glass fibre-reinforced material is investigated by computed tomography and the resultant pulling forces are measured. The results clearly show the correlation between the forming element temperature and the resulting forces due to a change in the viscosity of the thermoplastic matrix and the resulting fiber matrix interaction. In addition, the evaluation of the measurement data shows which forming forces are required to change the shape of the thermoplastic unidirectional material with a rectangular cross-section to a round one.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Pin Extrusion for Mechanical Joining from Orbital Formed Tailored Blanks with Local Material Pre-Distribution - Römisch, David; Hetzel, Andreas; Wituschek, Simon; Lechner, Michael; Merklein, Marion (Journal of Manufacturing and Materials Processing)
Pin extrusion is a common process to realise pin structures in different geometrical dimensions for a subsequent joining operation. Nevertheless, the process of pin extrusion offers process limits regarding sheet thinning as a consequence of the punch penetration depth into the sheet. Thereby, cracks at the residual sheet thickness can occur during strength tests, resulting in a failure of the complete joint due to severe thinning. Therefore, measures have to be taken into account to reduce the thinning. One possibility is the application of orbital formed tailored blanks with a local material pre-distribution, which allows a higher sheet thickness in the desired area. Within this contribution, the novel approach of a process combination of orbital forming and pin extrusion is investigated. To reveal the potential of a local material pre-distribution, conventional specimens are compared with previously orbital formed components. Relevant parameters such as the residual sheet thickness, the pin height as well as the average hardness values are compared. The results show a significant positive influence of a local material pre-distribution on the residual sheet thickness as well as the resulting pin height. Furthermore, the strain hardening during orbital forming can be seen as an additional advantage. To conclude the results, the process limits of conventional pin extrusion can be expanded significantly by the application of specimens with a local material pre-distribution.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Mechanics of Materials

Warmforming Flow Pressing Characteristics of Continuous Fibre Reinforced Thermoplastic Composites - Gröger, Benjamin; Römisch, David; Kraus, Martin; Troschitz, Juliane; Füßel, René; Merklein, Marion; Gude, Maik (Polymers)
The paper presents research regarding a thermally supported multi-material clinching process (hotclinching) for metal and thermoplastic composite (TPC) sheets: an experimental approach to investigate the flow pressing phenomena during joining. Therefore, an experimental setup is developed to compress the TPC-specimens in out-of-plane direction with different initial TPC thicknesses and varying temperature levels. The deformed specimens are analyzed with computed tomography to investigate the resultant inner material structure at different compaction levels. The results are compared in terms of force-compaction-curves and occurring phenomena during compaction. The change of the material structure is characterized by sliding phenomena and crack initiation and growth.
Keywords: Polymers and Plastics; General Chemistry

A Data Driven Modelling Approach for the Strain Rate Dependent 3D Shear Deformation and Failure of Thermoplastic Fibre Reinforced Composites: Experimental Characterisation and Deriving Modelling Parameters - Gerritzen, Johannes; Hornig, Andreas; Gröger, Benjamin; Gude, Maik (Journal of Composites Science)
The 3D shear deformation and failure behaviour of a glass fibre reinforced polypropylene in a shear strain rate range of γ˙=2.2×10−4 to 3.4 1s is investigated. An Iosipescu testing setup on a servo-hydraulic high speed testing unit is used to experimentally characterise the in-plane and out-of-plane behaviour utilising three specimen configurations (12-, 13- and 31-direction). The experimental procedure as well as the testing results are presented and discussed. The measured shear stress–shear strain relations indicate a highly nonlinear behaviour and a distinct rate dependency. Two methods are investigated to derive according material characteristics: a classical engineering approach based on moduli and strengths and a data driven approach based on the curve progression. In all cases a Johnson–Cook based formulation is used to describe rate dependency. The analysis methodologies as well as the derived model parameters are described and discussed in detail. It is shown that a phenomenologically enhanced regression can be used to obtain material characteristics for a generalising constitutive model based on the data driven approach.
Keywords: Engineering (miscellaneous); Ceramics and Composites

Atomic Force Microscope with an Adjustable Probe Direction and Integrated Sensing and Actuation - Schaude, Janik; Hausotte, Tino (Nanomanufacturing and Metrology)
This article presents the application and evaluation of a cantilever with integrated sensing and actuation as part of an atomic force microscope (AFM) with an adjustable probe direction, which is integrated into a nano measuring machine (NMM-1). The AFM, which is operated in closed-loop intermittent contact mode, is based on two rotational axes that enable the adjustment of the probe direction to cover a complete hemisphere. The axes greatly enlarge the metrology frame of the measuring system by materials with a comparatively high coefficient of thermal expansion, which ultimately limits the achievable measurement uncertainty of the measuring system. Thus, to reduce the thermal sensitivity of the system, the redesign of the rotational kinematics is mandatory. However, in this article, some preliminary investigations on the application of a self-sensing cantilever with an integrated micro heater for its stimulation will be presented. In previous investigations, a piezoelectric actuator has been applied to stimulate the cantilever. However, the removal of the piezoelectric actuator, which is enabled by the application of a cantilever with an integrated micro heater, promises an essential simplification of the sensor holder. Thus, in the future it might be possible to use materials with a low coefficient of thermal expansion, which are often difficult to machine and therefore only allow for rather simple geometries. Furthermore, because of the creepage of piezoelectric actuators, their removal from the metrology frame might lead to improved metrological characteristics. As will be shown, there are no significant differences between the two modes of actuation. Therefore, the redesigned rotational system will be based on the cantilever with integrated sensing and actuation.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering; Materials Science (miscellaneous)

A Damage Model for Corrosion Fatigue Due to Hydrogen Embrittlement - Shi, Yuhao; Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Material Modeling and Structural Mechanics)
Predicting the durability of components subjected to mechanical load under environmental conditions leading to corrosion is one of the most challenging tasks in mechanical engineering. The demand for precise predictions increases with the desire of lightweight design in transportation due to environmental protection. Corrosion with its manifold of mechanisms often occurs together with the production of hydrogen by electrochemical reactions. Hydrogen embrittlement is one of the most feared damage mechanisms for metal constructions often leading to early and unexpected failure. Until now, predictions are mostly based on costly experiments. Hence, a rational predictive model based on the fundamentals of electrochemistry and damage mechanics has to be developed in order to reduce the costs. In this work, a first model approach based on classical continuum damage mechanics is presented to couple both, the damage induced by the mechanical stress and the hydrogen embrittlement. An elaborated two-scale model based on the selfconsistent theory is applied to describe the mechanical damage due to fatigue. The electrochemical kinetics are elucidated through the Langmuir adsorption isotherm and the diffusion equation to consider the impact of hydrogen embrittlement on the fatigue. The modeling of the mechanism of hydrogen embrittlement defines the progress of damage accumulation due to the electrochemistry. The durability results like the S-N diagram show the influence of hydrogen embrittlement by varying, e.g. the fatigue frequency or the stress ratio.
Keywords: Hydrogen embrittlement; Fatigue; Continuum damage mechanics; Numerical simulation; Multi-field problem

Long-Term Behavior of Clinched Electrical Contacts - Kalich, Jan; Matzke, Marcus; Pfeiffer, Wolfgang; Schlegel, Stephan; Kornhuber, Ludwig; Füssel, Uwe (Metals)
Joining by forming operations presents powerful and complex joining techniques. Clinching is a well-known joining process for use in sheet metalworking. Currently, clinched joints are focusing on mechanically enhanced connections. Additionally, the demand for integrating electrical requirements to transmit electrical currents will be increased in the future. This integration is particularly important, for instance, in the e-mobility sector. It enables connecting battery cells with electrical joints of aluminum and copper. Systematic use of the process-specific advantages of this joining method opens up the possibility to find and create electrically optimized connections. The optimization for the transmission of electrical currents will be demonstrated for clinched joints by adapting the tool geometry and the clinched joint design. Based on a comparison of the electrical joint resistance, the limit use temperature is defined for the joining materials used based on the microstructural condition and the aging condition due to artificial aging. As a result of the investigations carried out, reliable current transmission at a constant conductor temperature of up to 120 °C can be achieved for clinched copper–copper joints. In the case of pure aluminum joints and mixed joints of aluminum and copper, long-term stable current transmission can be ensured up to a conductor temperature of 100 °C.
Keywords: General Materials Science; Metals and Alloys

Modelling and Simulation Strategies for Fluid–Structure-Interactions of Highly Viscous Thermoplastic Melt and Single Fibres—A Numerical Study - Gröger, Benjamin; Wang, Jingjing; Bätzel, Tim; Hornig, Andreas; Gude, Maik (Materials)
A virtual test setup for investigating single fibres in a transverse shear flow based on a parallel-plate rheometer is presented. The investigations are carried out to verify a numerical representation of the fluid–structure interaction (FSI), where Arbitrary Lagrangian–Eulerian (ALE) and computational fluid dynamics (CFD) methods are used and evaluated. Both are suitable to simulate flexible solid structures in a transverse shear flow. Comparative investigations with different model setups and increasing complexity are presented. It is shown, that the CFD method with an interface-based coupling approach is not capable of handling small fibre diameters in comparison to large fluid domains due to mesh dependencies at the interface definitions. The ALE method is more suited for this task since fibres are embedded without any mesh restrictions. Element types beam, solid, and discrete are considered for fibre modelling. It is shown that the beam formulation for ALE and 3D solid elements for the CFD method are the preferred options.
Keywords: General Materials Science

Comparison of two mesh-moving techniques for finite element simulations of galvanic corrosion - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Acta Mechanica)
Galvanic corrosion is a destructive process between dissimilar metals. The present paper presents a constructed numerical test case to simulate galvanic corrosion of two dissimilar metals. This test case is used to study the accuracy of different implementations to track the dissolving anode boundary. One technique is to numerically simulate a mesh displacement based on the prescribed displacement at the anode boundary. The second method is to adjust only the boundary elements. Re-meshing after a certain number of time steps is applied to both implementations. They produce similar results for an electrical and electrochemical field problem. This work shows that mesh smoothing does not result in higher accuracy when modeling a moving anode front. Adjusting only the boundary elements is sufficient when frequent re-meshing is used.
Keywords: Mechanical Engineering; Computational Mechanics

Electrical Contacting of Aluminum Bus Bars Using Clinching and Functional Elements - Füssel, Uwe; Schlegel, Stephan; Reschke, Gregor; Kalich, Jan (SFU/ICAFT 2022)
As a joining-by-forming process, clinching and the use of functional elements enable low-energy joining of components through form, force, and, under certain conditions, material closure. In addition to the transmission of mechanical forces, these joining processes can be qualified for additional electrical contact within the scope of functional integration for electro-mobile applications. For this purpose, maximizing the force and material closure is necessary to ensure a long-term, stable transmission of electrical currents. To this end, the electrical properties of the joints were optimized. The investigations carried out show the long-term behavior under normal operating conditions and the short-circuit case.

Investigations on Combined in situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Robust estimation of clinch joint characteristics based on data-driven methods - Zirngibl, Christoph; Schleich, Benjamin; Wartzack, Sandro (The International Journal of Advanced Manufacturing Technology)
Given a steadily increasing demand on multi-material lightweight designs, fast and cost-efficient production technologies, such as the mechanical joining process clinching, are becoming more and more relevant for series production. Since the application of such joining techniques often base on the ability to reach similar or even better joint loading capacities compared to established joining processes (e.g., spot welding), few contributions investigated the systematic improvement of clinch joint characteristics. In this regard, the use of data-driven methods in combination with optimization algorithms showed already high potentials for the analysis of individual joints and the definition of optimal tool configurations. However, the often missing consideration of uncertainties, such as varying material properties, and the related calculation of their impact on clinch joint properties can lead to poor estimation results and thus to a decreased reliability of the entire joint connection. This can cause major challenges, especially for the design and dimensioning of safety-relevant components, such as in car bodies. Motivated by this, the presented contribution introduces a novel method for the robust estimation of clinch joint characteristics including uncertainties of varying and versatile process chains in mechanical joining. Therefore, the utilization of Gaussian process regression models is demonstrated and evaluated regarding the ability to achieve sufficient prediction qualities.
Keywords: Industrial and Manufacturing Engineering; Computer Science Applications; Mechanical Engineering; Software; Control and Systems Engineering

Numerical fatigue life prediction of corroded and non-corroded clinched joints - Harzheim, Sven; Hofmann, Martin; Wallmersperger, Thomas (Mechanics of Advanced Materials and Structures)
Mechanical clinching is used to create lightweight hybrid structures. In order to estimate the service life of clinched components, its fatigue properties need to be known under different mechanical loading conditions. In addition to fatigue, corrosion is another factor that affects the fatigue life of clinched joints. In the literature, many corrosion and high-cycle fatigue damage models exist. However, little is known about how both phenomena interact in clinched joints. In this article, the influence of galvanic corrosion on clinched EN AW-6014/HCT590X + Z sheets on the fatigue life is investigated by means of numerical simulations and experimental results. An accurate prediction of the Wöhler lines of non-corroded and pre-corroded clinched specimens is shown.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science; General Mathematics; Civil and Structural Engineering

Experimental Measurement Method and Evaluation of an Analytical Approach for Sound Conduction through Multiple Clinched Sheets - Stephan, Richard; Brosius, Alexander (The 28th Saxon Conference on Forming Technology SFU and the 7th International Conference on Accuracy in Forming Technology ICAFT)
The conduction of structure-borne sound through joints causes energy dissipation. The sound reduction index describes this energy loss as a level decrease in the particle velocity across series-connected damping elements for which the superposition principle applies. This simple model can help to develop a testing method for joints based on this characteristic energy loss. In this paper, this model is experimentally evaluated for multiple in-series clinched aluminium sheets. Samples connected by several clinch points arranged in parallel are investigated experimentally, and the results are discussed.
Keywords: clinching; mechanical joining; damping; model; evaluation; dynamics

Experimental and Numerical Analysis of Cold Formed Multi Pin Structures Using a Multi-Acting Tool Design - Römisch, David; Merklein, Marion

Versatile tool design for a tumbling self-piercing riveting process - Wituschek, Simon; Lechner, Michael

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-destructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Calibration of 3D scan trajectories for an industrial computed tomography setup with 6-DOF object manipulator system using a single sphere - Butzhammer, Lorenz; Müller, Andreas Michael; Hausotte, Tino (Measurement Science and Technology)
In industrial x-ray computed tomography (CT), the application of more complex scan paths in comparison to the typical circular trajectory (${360}^{°}$ rotation of the measurement object) can extend the potential of CT. One way to enable such 3D scan trajectories is to use a 6-degrees-of-freedom (DOF) object manipulator system. In our case, a hexapod is mounted on top of the rotary table of a commercial CT scanner. This allows for adaptive tilting of the measurement object during the scan. For high accuracy, the geometry calibration of such setups is typically done using the x-ray projections of a calibrated multi-sphere object. Contrary to this, here, we demonstrate a procedure that is based on only a single sphere and can therefore experimentally be implemented with low effort. Using the intrinsic geometry parameters of the CT device as prior information, the hexapod coordinate system with respect to the CT machine coordinate system is determined by means of a one-step optimization approach. The resulting parameters are used to calculate projection matrices that enable the volume reconstruction for 3D scan trajectories. The method is validated using simulated x-ray images and experimental investigations including dimensional measurements. For the used setup, geometric measurement results for 3D scan trajectories that are calibrated with the presented method show in sum increased errors compared to the circular scans. A limited pose accuracy of the manipulator system is discussed as a potential cause. The results nevertheless indicate that the presented method is generally feasible for dimensional CT measurements provided that the pose accuracy is sufficient. The calibration procedure can therefore be a low-cost and easier to implement alternative compared to trajectory calibration methods based on multi-sphere objects, but with a tendency towards lower measurement accuracy. The methodology can in principle be transferred to different setups with 6-DOF manipulator systems, e.g. C-arm CT devices with a robot arm.
Keywords: Applied Mathematics; Instrumentation; Engineering (miscellaneous)

Functionality Study of an Optical Measurement Concept for Local Force Signal Determination in High Strain Rate Tensile Tests - Böhnke, Max; Unruh, Eduard; Sell, Stanislaw; Bobbert, Mathias; Hein, David; Meschut, Gerson (Key Engineering Materials)
Many mechanical material properties show a dependence on the strain rate, e.g. yield stress or elongation at fracture. The quantitative description of the material behavior under dynamic loading is of major importance for the evaluation of crash safety. This is carried out using numerical methods and requires characteristic values for the materials used. For the standardized determination of dynamic characteristic values in sheet metal materials, tensile tests performed according to the guideline from [1]. A particular challenge in dynamic tensile tests is the force measurement during the test. For this purpose, strain gauges are attached on each specimen, wired to the measuring equipment and calibrated. This is a common way to determine a force signal that is as low in vibration and as free of bending moments as possible. The preparation effort for the used strain gauges are enormous. For these reasons, an optical method to determine the force by strain measurement using DIC is presented. The experiments are carried out on a high speed tensile testing system. In combioantion with a 3D DIC high speed system for optical strain measurement. The elastic deformation of the specimen in the dynamometric section is measured using strain gauges and the optical method. The measured signals are then compared to validate the presented method. The investigations are conducted using the dual phase steel material HCT590X and the aluminum material EN AW-6014 T4. Strain rates of up to 240 s-1 are investigated.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Development of a Modified Punch Test for Investigating the Failure Behavior in Sheet Metal Materials - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)

Experimental and numerical investigation of the influence of multiaxial loading conditions on the failure behavior of clinched joints - Böhnke, Max; Bielak, Christian Roman; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)

Fracture mechanical investigation of preformed metal sheets using a novel CC-specimen - Weiß, Deborah; Schramm, Britta (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

Review on mechanical joining by plastic deformation - Meschut, Gerson; Merklein, M.; Brosius, A.; Drummer, D.; Fratini, L.; Füssel, U.; Gude, M.; Homberg, Werner; Martins, P.A.F.; Bobbert, Mathias; Lechner, M.; Kupfer, R.; et al. (Journal of Advanced Joining Processes)
Mechanical joining technologies are increasingly used in multi-material lightweight constructions and offer opportunities to create versatile joining processes due to their low heat input, robustness to metallurgical incompatibilities and various process variants. They can be categorised into technologies which require an auxiliary joining element, or do not require an auxiliary joining element. A typical example for a mechanical joining process with auxiliary joining element is self-piercing riveting. A wide range of processes exist which are not requiring an auxiliary joining element. This allows both point-shaped (e.g., by clinching) and line-shaped (e.g., friction stir welding) joints to be produced. In order to achieve versatile processes, challenges exist in particular in the creation of intervention possibilities in the process and the understanding and handling of materials that are difficult to join, such as fiber reinforced plastics (FRP) or high-strength metals. In addition, predictive capability is required, which in particular requires accurate process simulation. Finally, the processes must be measured non-destructively in order to generate control variables in the process or to investigate the cause-effect relationship. This paper covers the state of the art in scientific research concerning mechanical joining and discusses future challenges on the way to versatile mechanical joining processes.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Geometric and mechanical joint characterization of conventionally and tumbled self-piercing riveting joints - Wituschek, Simon; Kappe, Fabian; Meschut, Gerson; Lechner, Michael (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In view of economic and ecological trends, the concepts for lightweight construction in transport systems are becoming increasingly important. These are frequently applied in the form of multi-material systems, which are characterized by the selective use of materials and geometries. One major challenge in the manufacturing of multi-material systems is the joining of the individual components to form a complete system. Mechanical joining processes such as semi-tubular self-piercing riveting are frequently used for this application but reach their limits concerning the number of combinations of geometry and material. In order to react to the requirements and to increase the versatility of semi-tubular self-pierce riveting, a process combination consisting of a tumbling process and a self-pierce riveting process has been presented previously. This process combination is used in this work to investigate the versatility and to identify the influencing parameters on it. For this purpose, experiments are conducted to identify process-side influence possibilities. The tests are performed with a dual-phase steel aluminum alloy to represent the varying mechanical characteristics of multi-material systems. Furthermore, the initial sheet thicknesses of the joining partners are varied in several steps. In addition to the geometric joint formation used to describe the undercut, the rivet head end position and the residual sheet thickness, the joining process, is also analyzed during the investigations. Further, the innovative joining process is evaluated by comparing it with a conventional self-piercing riveting process. The knowledge obtained represents a basis for the identification and evaluation of the versatility of the process combination.
Keywords: Mechanical Engineering; General Materials Science

Mechanical Properties and Joinability of AlSi9 Alloy Manufactured by Twin‐Roll Casting - Neuser, Moritz; Kappe, Fabian; Ostermeier, Jakob; Krüger, Jan Tobias; Bobbert, Mathias; Meschut, Gerson; Schaper, Mirko; Grydin, Olexandr (Advanced Engineering Materials)
Keywords: Condensed Matter Physics; General Materials Science

Identification of Requirements for FE Modeling of an Adaptive Joining Technology Employing Friction-Spun Joint Connectors (FSJC) - Oesterwinter, Annika; Wischer, Christian; Homberg, Werner (Metals)
The adaptive joining process employing friction-spun joint connectors (FSJC) is a promising method for the realization of adaptable joints and thus for lightweight construction. In addition to experimental investigations, numerical studies are indispensable tools for its development. Therefore, this paper includes an analysis of boundary conditions for the spatial discretization and mesh modeling techniques, the material modeling, the contact and friction modeling, and the thermal boundary conditions for the finite element (FE) modeling of this joining process. For these investigations, two FE models corresponding to the two process steps were set up and compared with the two related processes of friction stir welding and friction drilling. Regarding the spatial discretization, the Lagrangian approach is not sufficient to represent the deformation that occurs. The Johnson-Cook model is well suited as a material model. The modeling of the contact detection and friction are important research subjects. Coulomb’s law of friction is not adequate to account for the complex friction phenomena of the adaptive joining process. The thermal boundary conditions play a decisive role in heat generation and thus in the material flow of the process. It is advisable to use temperature-dependent parameters and to investigate in detail the influence of radiation in the entire process.
Keywords: General Materials Science; Metals and Alloys

Further Development of 3D Crack Growth Simulation Program to Include Contact Loading Situations - Joy, Tintu David; Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Applied Sciences)
Crack growth in structures depends on the cyclic loads applied on it, such as mechanical, thermal and contact, as well as residual stresses, etc. To provide an accurate simulation of crack growth in structures, it is of high importance to integrate all kinds of loading situations in the simulations. Adapcrack3D is a simulation program that can accurately predict the propagation of cracks in real structures. However, until now, this three-dimensional program has only considered mechanical loads and static thermal loads. Therefore, the features of Adapcrack3D have been extended by including contact loading in crack growth simulations. The numerical simulation of crack propagation with Adapcrack3D is generally carried out using FE models of structures provided by the user. For simulating models with contact loading situations, Adapcrack3D has been updated to work with FE models containing multiple parts and necessary features such as coupling and surface interactions. Because Adapcrack3D uses the submodel technique for fracture mechanical evaluations, the architecture of the submodel is also modified to simulate models with contact definitions between the crack surfaces. This paper discusses the newly implemented attribute of the program with the help of illustrative examples. The results confirm that the contact simulation in Adapcrack3D is a major step in improving the functionality of the program.
Keywords: Fluid Flow and Transfer Processes; Computer Science Applications; Process Chemistry and Technology; General Engineering; Instrumentation; General Materials Science

Influence of plane mixed-mode loading on the kinking angle of clinchable metal sheets - Weiß, Deborah; Schramm, Britta; Kullmer, Gunter (Procedia Structural Integrity)
Keywords: General Engineering; Energy Engineering and Power Technology

A Review on the Modeling of the Clinching Process Chain - Part III: Operational Phase - Schramm, Britta; Harzheim, Sven; Weiß, Deborah; Joy, Tintu David; Hofmann, Martin; Mergheim, Julia; Wallmersperger, Thomas (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Development of a method for the separate measurement of the growth of internal crack tips by means of the potential drop method - Kullmer, Gunter; Weiß, Deborah; Schramm, Britta (Engineering Fracture Mechanics)
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Joining of multi-material structures using a versatile self-piercing riveting process - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Production Engineering)
Due to the increasing use of multi-material constructions and the resulting material incompatibilities, mechanical joining technologies are gaining in importance. The reasons for this are the variety of joining possibilities as well as high load-bearing capacities. However, the currently rigid tooling systems cannot react to changing boundary conditions, such as changed sheet thicknesses or strength. For this reason, a large number of specialised joining processes have been developed to expand the range of applications. Using a versatile self-piercing riveting process, multi-material structures are joined in this paper. In this process, a modified tool actuator technology is combined with multi-range capable auxiliary joining parts. The multi-range capability of the rivets is achieved by forming the rivet head onto the respective thickness of the joining part combination without creating a tooling set-up effort. The joints are investigated both experimentally on the basis of joint formation and load-bearing capacity tests as well as by means of numerical simulation. It turned out that all the joints examined could be manufactured according to the defined standards. The load-bearing capacities of the joints are comparable to those of conventionally joined joints. In some cases the joint fails prematurely, which is why lower energy absorptions are obtained. However, the maximum forces achieved are higher than those of conventional joints. Especially in the case of high-strength materials arranged on the die side, the interlock formation is low. In addition, the use of die-sided sheets requires a large deformation of the rivet head protrusion, which leads to an increase in stress and, as a result, to damage if the rivet head. However, a negative influence on the joint load-bearing capacity could be excluded.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Provision of cross-domain knowledge in mechanical joining using ontologies - Zirngibl, Christoph; Kügler, Patricia; Popp, Julian; Bielak, Christian Roman; Bobbert, Mathias; Drummer, Dietmar; Meschut, Gerson; Wartzack, Sandro; Schleich, Benjamin (Production Engineering)
Since the application of mechanical joining methods, such as clinching or riveting, offers a robust solution for the generation of advanced multi-material connections, the use in the field of lightweight designs (e.g. automotive industry) is steadily increasing. Therefore, not only the design of an individual joint is required but also the dimensioning of the entire joining connection is crucial. However, in comparison to thermal joining techniques, such as spot welding, the evaluation of the joints’ resistance against defined requirements (e.g. types of load, minimal amount of load cycles) mainly relies on the consideration of expert knowledge, a few design principles and a small amount of experimental data. Since this generally implies the involvement of several domains, such as the material characterization or the part design, a tremendous amount of data and knowledge is separately generated for a certain dimensioning process. Nevertheless, the lack of formalization and standardization in representing the gained knowledge leads to a difficult and inconsistent reuse, sharing or searching of already existing information. Thus, this contribution presents a specific ontology for the provision of cross-domain knowledge about mechanical joining processes and highlights two potential use cases of this ontology in the design of clinched and pin joints.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Numerical Investigation of the Influence of a Movable Die Base on Joint Formation in Semi-tubular Self-piercing Riveting - Kappe, Fabian; Wituschek, Simon; de Pascalis, Vincenzo; Bobbert, Mathias; Lechner, Michael; Meschut, Gerson (Materials Design and Applications IV)
Due to economic and ecological requirements and the associated trend towards lightweight construction, mechanical joining technologies like self-piercing riveting are gaining in importance. In addition, the increase in lightweight multi-material joints has led to the development of many different mechanical joining technologies which can only be applied to join a small number of material combinations. This leads to low process efficiency, and in the case of self-piercing riveting, to a large number of required tool changes. Another approach focuses on reacting to changing boundary conditions as well as the creation of customised joints by using adaptive tools, versatile auxiliary joining parts or modified process kinematics. Therefore, this study investigates the influence of increased die-sided kinematics on joint formation in self-piercing riveting process. The aim is to achieve an improvement of the joint properties by superimposing the punch feed. Furthermore, it is intended to reduce required tool changes due to the improved joint design. The investigations were carried out by means of a 2D-axisymmetric numerical simulation model using the LS-Dyna simulation software. After the validation of the process model, the die was extended to include driven die elements. Using the model, different kinematics as well as their effects on the joint formation and the internal stress concentration could be analysed. In principle, the increased actuator technology enabled an increase of the interlock formation for both pure aluminium and multi-material joints consisting of steel and aluminium. However, the resulting process forces were higher during the process phases of punching and spreading.

Determining the influence of different process parameters on the versatile self-piercing riveting process using numerical methods - Kappe, Fabian; Zirngibl, Christoph; Schleich, Benjamin; Bobbert, Mathias; Wartzack, Sandro; Meschut, Gerson (Journal of Manufacturing Processes)
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management

Increasing flexibility of self-piercing riveting by reducing tool–geometry combinations using cluster analysis in the application of multi-material design - Kappe, Fabian; Schadow, Luca; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers Part L Journal of Materials Design and Applications)

Determining the properties of multi‑range semi‑tubular self‑piercing riveted joints - Kappe, Fabian; Wituschek, Simon; Bobbert, Mathias; Meschut, Gerson (Production Engineering)

Fracture mechanical evaluation of the material HCT590X - Schramm, Britta; Weiß, Deborah (Materials Testing)
For a reliable, strength-compliant and fracture-resistant design of components and technical structures and for the prevention of damage cases, both the criteria of strength calculation and fracture mechanics are essential. In contrast to strength calculation the fracture mechanics assumes the existence of cracks which might further propagate due to the operational load. First, the present paper illustrates the general procedure of a fracture mechanical evaluation of fatigue cracks in order to assess practical damage cases. Fracture mechanical fundamentals which are essential for the calculation of the stress intensity factors K I and the experimental determination of fracture mechanical material parameters (e.g. threshold Δ K I,th against fatigue crack growth, crack growth rate curve) are explained in detail. The subsequent fracture mechanical evaluation on the basis of the local stress situation at the crack tip and the fracture mechanical material data is executed for different materials and selected crack problems. Hereby, the main focus is on the material HCT590X as it is the essential material being investigated by TRR285.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Development of a Numerical 3D Model for Analyzing Clinched Joints in Versatile Process Chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (The Minerals, Metals & Materials Series)
The application of the mechanical joining process clinching enables the joining of sheet metals with a wide range of material-thickness configurations, which is of interest in lightweight construction of multi-material structures. Each material-thickness combination results in a joint with its own property profile that is affected differently by variations. Manufacturing process-related effects from preforming steps influence the geometric shape of a clinched joint as well as its load-bearing capacity. During the clinching process high degrees of plastic strain, increased temperatures and high strain rates occur. In this context, a 3D numerical model was developed which can represent the material-specific behaviour during the process chain steps sheet metal forming, joining, and loading phase in order to achieve a high predictive accuracy of the simulation. Besides to the investigation of the prediction accuracy, the extent of the influence of individual modelling aspects such as temperature and strain rate dependency is examined.

Numerical investigation of a friction test to determine the friction coefficients for the clinching process - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
Clinching as a mechanical joining process has become established in many areas of car body. In order to predict relevant properties of clinched joints and to ensure the reliability of the process, it is numerically simulated during the product development process. The prediction accuracy of the simulated process depends on the implemented friction model. Therefore, a new method for determining friction coefficients in sheet metal materials was developed and tested. The aim of this study is the numerical investigation of this experimental method by means of FE simulation. The experimental setup is modelled in a 3D numerical simulation taking into account the process parameters varying in the experiment, such as geometric properties, contact pressure and contact velocity. Furthermore, the contact description of the model is calibrated via the experimentally determined friction coefficients according to clinch-relevant parameter space. It is shown that the assumptions made in the determination of the experimental data in preliminary work are valid. In addition, it is investigated to what extent the standard Coulomb friction model in the FEM can reproduce the results of the experimental method.
Keywords: Mechanical Engineering; General Materials Science

A Review on the Modeling of the Clinching Process Chain - Part I: Design Phase - Schramm, Britta; Martin, Sven; Steinfelder, Christian; Bielak, Christian Roman; Brosius, Alexander; Meschut, Gerson; Tröster, Thomas; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

A Review on the Modeling of the Clinching Process Chain - Part II: Joining Process - Schramm, Britta; Friedlein, Johannes; Gröger, Benjamin; Bielak, Christian Roman; Bobbert, Mathias; Gude, Maik; Meschut, Gerson; Wallmersperger, Thomas; Mergheim, Julia (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical investigation of the clinched joint loadings considering the initial pre-strain in the joining area - Martin, Sven; Bielak, Christian Roman; Bobbert, Mathias; Tröster, Thomas; Meschut, Gerson (Production Engineering)
The components of a body in white consist of many individual thin-walled sheet metal parts, which usually are manufactured in deep-drawing processes. In general, the conditions in a deep-drawing process change due to changing tribology conditions, varying degrees of spring back, or scattering material properties in the sheet blanks, which affects the resulting pre-strain. Mechanical joining processes, especially clinching, are influenced by these process-related pre-strains. The final geometric shape of a clinched joint is affected to a significant level by the prior material deformation when joining with constant process parameters. That leads to a change in the stiffness and force transmission in the clinched joint due to the different geometric dimensions, such as interlock, neck thickness and bottom thickness, which directly affect the load bearing capacity. Here, the influence of the pre-straining in the deep drawing process on the force distribution in clinch points in an automotive assembly is investigated by finite-element models numerically. In further studies, the results are implemented in an optimization tool for designing clinched components. The methodology starts with a pre-straining of metal sheets. This step is followed by 2D rotationally symmetric forming simulations of the joining process. The resulting mesh of each forming simulation is rotated and 3D models are obtained. The clinched joint solid model with pre-strains is used further to determine the joint stiffnesses. With the simulation of the same test set-up with an equivalent point-connector model, the equivalent stiffness for each pre-strain combination is determined. Simulations are performed on a clinched component to assess the influence of pre-strain and sheet thinning on the clinched joint loadings by using the equivalent stiffnesses. The investigations clearly show that for the selected component, the loadings at the clinch points are dependent on the sheet thinning and the stiffnesses due to pre-strain. The magnitude of the influence varies depending on the quantity considered. For example, the shear force is more sensitive to the joint stiffness than to the sheet thinning.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Influence of the Surrounding Sheet Geometry on a Clinched Joint - Martin, Sven; Kurtusic, Kristijan; Tröster, Thomas (Key Engineering Materials)

Investigations on Combined In Situ CT and Acoustic Analysis during Clinching - Köhler, Daniel; Stephan, Richard; Kupfer, Robert; Troschitz, Juliane; Brosius, Alexander; Gude, Maik (Key Engineering Materials)
Clinching is a cost efficient method for joining components in series production. To assure the clinch point’s quality, the force displacement curve during clinching or the bottom thickness are monitored. The most significant geometrical characteristics of the clinch point, neck thickness and undercut, are usually tested destructively by microsectioning. However, micrograph preparation goes ahead with a resetting of elastic deformations and crack-closing after unloading. To generate a comprehensive knowledge of the clinch point’s inner geometry under load, in-situ computed tomography (CT) and acoustic testing (TDA) can be combined. While the TDA is highly sensitive to the inner state of the clinch point, it could detect critical events like crack development during loading. If such events are indicated, the loading process is stopped and a stepped in-situ CT of the following crack and deformation development is performed. In this paper, the concept is applied to the process of clinching itself, providing a detailed three-dimensional insight in the development of the joining zone. A test set-up is used which allows a stepwise clinching of two aluminium sheets EN AW 6014. Furthermore, this set-up is positioned within a CT system. In order to minimize X-ray absorption, a beryllium cylinder is used within the set-up frame and clinching tools are made from Si3N4. The actuator and sensor necessary for the TDA are integrated in the set-up. In regular process steps, the clinching process is interrupted in order to perform a TDA and a CT scan. In order to enhance the visibility of the interface, a thin tin layer is positioned between the sheets prior clinching. It is shown, that the test-set up allows a monitoring of the dynamic behaviour of the specimen during clinching while the CT scans visualize the inner geometry and material flow non-destructively.
Keywords: Mechanical Engineering; Mechanics of Materials; General Materials Science

Approach to Determine the Characteristic Dimensions of Clinched Joints by Industrial X-ray Computed Tomography - Busch, Matthias; Köhler, Daniel; Hausotte, Tino; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (e-Journal of Nondestructive Testing)
Destructive micrograph analysis (MA) is the standard method for the assessment of clinched joints. However, during the joint preparation for the MA, geometric features of the joint can change due to elastic effects and closing cracks. X-ray computed tomography (CT) is a promising alternative to investigate the joint non-estructively. However, if the material properties of similar joining partners are the same, the CT is not able to correctly resolve surfaces in the joint that are close to or pressing onto each other. These surfaces are relevant for the determination of characteristic dimensions such as neck thickness and undercut. By placing a thin, highly radiopaque tin layer between the joining partners, the interfacial area in the reconstructed volume can be highlighted. In this work, a method for the localisation of the tin layer inside the joint as well as threshold value procedures for the outer joint contour in cross section images are investigated. The measured characteristic dimensions are compared with measured values from MA of the same samples and of samples without tin layer. In addition, possible effects of the tin layer on the joining point characteristics as well as problems of the MA are discussed.

Untersuchung zum Einfluss radioopaker Zwischenschichten bei der in-situ CT geclinchter Verbindungen - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (Tagungsband zur Werkstoffprüfung 2022)
Zur Qualitätssicherung von Clinchpunkten werden häufig ex-situ Methoden, wie etwa Schliffbildanalysen, eingesetzt. Diese ermöglichen jedoch nicht die Berücksichtigung von Phänomenen, die während der Belastung auftreten, da sich nach der Entlastung elastische Deformationen zurückbilden und Risse wieder schließen. Dagegen kann mit der in-situ Computertomographie (CT) der innere Deformationszustand des Clinchpunkts, z.B. während eines Scherzugversuchs, untersucht werden. Hierbei ist es für artgleiche Werkstoffe aufgrund der hohen Pressungen im Clinchpunkt schwierig, die Trennfläche zwischen den Fügepartnern im CT-Scan zu erkennen. Daher wird eine radioopake Zwischenschicht aus Zinn in die Trennfläche eingebracht. In dieser Arbeit wird der Einfluss der Zwischenschicht auf die in-situ CT-Scherzugprüfung untersucht. Hierzu werden sowohl Kraft-Verlängerungs-Kurven als auch die Geometrie der Clinchpunkte während der Belastung verglichen.

Clinching in In Situ CT—A Novel Validation Method for Mechanical Joining Processes - Köhler, Daniel; Kupfer, Robert; Troschitz, Juliane; Gude, Maik (The Minerals, Metals & Materials Series)

Influence of heat treatment on the suitability for clinching of the aluminium casting alloy AlSi9 - Neuser, Moritz; Böhnke, Max; Grydin, Olexandr; Bobbert, Mathias; Schaper, Mirko; Meschut, Gerson (Proceedings of the Institution of Mechanical Engineers, Part L: Journal of Materials: Design and Applications)
In many manufacturing areas, multi-material designs are implemented in which individual components are joined together to form complex structures with numerous joints. For example, in the automotive sector, cast components are used at the junctions of the body and joined with different types of sheet metal and extruded profiles. To be able to join structures consisting of different materials, alternative joining technologies have emerged in recent years. This includes clinching, which allows assembling of two or more thin sheet metal and casting parts by solely cold forming the material. Clinching the brittle and usually less ductile cast aluminium alloys remains a challenge because the brittle character of the cast aluminium alloys can cause cracks during the forming of the clinched joint. In this study, the influence of the heat treatment time of an aluminium casting alloy AlSi9 on the joinability in the clinching process is investigated. Specific heat treatment of the naturally hard AlSi9 leads to a modification of the eutectic microstructure, which can increase ductility. Based on this, it will be examined if specific clinching die geometries can be used, which achieve an optimized geometrical formation of the clinched joint. The load-bearing capacities of the clinched joints are determined and compared by shear tensile and head tensile tests. Furthermore, the joints are examined microscopically to investigate the influence of the heat treatment on the failure behaviour during the load-bearing tests as well as crack initiation within the joining process.
Keywords: Mechanical Engineering; General Materials Science

Influence of solidification rates and heat treatment on the mechanical performance and joinability of the cast aluminium alloy AlSi10Mg - Neuser, Moritz; Grydin, Olexandr; Frolov, Y.; Schaper, Mirko (Production Engineering)
In modern vehicle chassis, multi-material design is implemented to apply the appropriate material for each functionality. In spaceframe technology, both sheet metal and continuous cast are joined to castings at the nodal points of the chassis. Since resistance spot welding is not an option when different materials are joined, research is focusing on mechanical joining methods for multi-material designs. To reduce weight and achieve the required strength, hardenable cast aluminium alloys of the AlSi-system are widely used. Thus, 85–90% of aluminium castings in the automotive industry are comprised of the AlSi-system. Due to the limited weldability, mechanical joining is a suitable process. For this application, various optimisation strategies are required to produce a crack-free joint, as the brittle character of the AlSi alloy poses a challenge. Thus, adapted castings with appropriate ductility are needed. Hence, in this study, the age-hardenable cast aluminium alloy AlSi10Mg is investigated regarding the correlation of the different thicknesses, the microstructural characteristics as well as the resulting mechanical properties. A variation of the thicknesses leads to different solidification rates, which in turn affect the microstructure formation and are decisive for the mechanical properties of the casting as well as the joinability. For the investigation, plates with thicknesses from 2.0 to 4.0 mm, each differing by 0.5 mm, are produced via sand casting. Hence, the overall aim is to evaluate the joinability of AlSi10Mg and derive conclusions concerning the microstructure and mechanical properties.
Keywords: Industrial and Manufacturing Engineering; Mechanical Engineering

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Numerical and Experimental Investigation of Heat Transfer in the Solidification-Deformation Zone During Twin-Roll Casting of Aluminum Strips - Grydin, Olexandr; Mortensen, Dag; Neuser, Moritz; Lindholm, Dag; Fjaer, Hallvard G.; Schaper, Mirko (Light Metals 2022)

Clinching of Aluminum Materials – Methods for the Continuous Characterization of Process, Microstructure and Properties - Kupfer, Robert; Köhler, Daniel; Römisch, David; Wituschek, Simon; Ewenz, Lars; Kalich, Jan; Weiß, Deborah; Sadeghian, Behdad; Busch, Matthias; Krüger, Jan Tobias; Neuser, Moritz; Grydin, Olexandr; et al. (Journal of Advanced Joining Processes)
Clinching as a mechanical joining technique allows a fast and reliable joining of metal sheets in large-scale production. An efficient design and dimensioning of clinched joints requires a holistic understanding of the material, the joining process and the resulting properties of the joint. In this paper, the process chain for clinching metal sheets is described and experimental techniques are proposed to analyze the process-microstructure-property relationships from the sheet metal to the joined structure. At the example of clinching aluminum EN AW 6014, characterization methods are applied and discussed for the following characteristics: the mechanical properties of the sheet materials, the tribological behavior in the joining system, the joining process and the resulting material structure, the load-bearing behavior of the joint, the damage and degradation as well as the service life and crack growth behavior. The compilation of the characterization methods gives an overview on the advantages and weaknesses of the methods and the multiple interactions of material, process and properties during clinching. In addition, the results of the analyses on EN AW 6014 can be applied for parameterization and validation of simulations.
Keywords: Mechanical Engineering; Mechanics of Materials; Engineering (miscellaneous); Chemical Engineering (miscellaneous)

Inverse parameter identification of an anisotropic plasticity model for sheet metal - Friedlein, J.; Wituschek, S.; Lechner, M.; Mergheim, J.; Steinmann, P. (IOP Conference Series: Materials Science and Engineering)
The increasing economic and ecological demands on the mobility sector require efforts to reduce resource consumption in both the production and utilization phases. The use of lightweight construction technologies can save material and increase energy efficiency during operation. Multi-material systems consisting of different materials and geometries are used to achieve weight reduction. Since conventional joining processes reach their limits in the connection of these components, new methods and technologies are necessary in order to be able to react versatilely to varying process and disturbance variables. For fundamental investigations of new possibilities in joining technology, numerical investigations are helpful to identify process parameters. To generate valid results, robust and efficient material models are developed which are adapted to the requirements of versatile joining technologies, for instance to the high plastic strains associated with self-piercing riveting. To describe the inherent strain-induced plastic orthotropy of sheet metal an anisotropic Hill-plasticity model is formulated. Tensile tests for different sheet orientations are conducted both experimentally and numerically to adjust the anisotropic material parameters by inverse parameter identification for aluminium EN AW-6014 and steel HCT590X. Then, the layer compression test is used to validate the model and the previously identified parameters.

Energy direction in ultrasonic impregnation of continuous fiber-reinforced thermoplastics - Popp, J.; Wolf, M.; Mattner, T.; Drummer, D. (Journal of Composites Science)
As a new and innovative processing method for fabrication for fiber-reinforced thermoplastic composites (CFRTs), the feasibility of ultrasonic welding technology was proven in several studies. This method offers potential for the direct manufacturing of CFRT–metal structures via embedded pin structures. Despite the previous studies, a deeper understanding of the process of energy input and whether fibers work as energy directors and consequently can, in combination with chosen processing parameters, influence the consolidation quality of the CFRTs, is still unknown. Consequently, the aim of this work is to establish a deeper process understanding of the ultrasonic direct impregnation of fiber-reinforced thermoplastics with an emphasis on the fiber’s function as energy directors. Based on the generated insights, a better assessment of the feasibility of direct, hybrid part manufacturing is possible. The produced samples were primarily evaluated by optical and mechanical test methods. It is demonstrated that with higher welding time and amplitude, a better consolidation quality can be achieved and that independent of the process parameters chosen in this study, no significant fiber breakage occurs. This is interpreted as a sign of a gentle impregnation process. Furthermore, based on the examination of single roving and 5-layer set-ups, it is shown that the glass fibers function as energy directors and can influence the transformation of sonic energy into thermal energy. In comparison to industrially available CFRT material, the mechanical properties are weaker, but materials and processes offer potential for significant improvement. Based on these findings, proposals for a direct impregnation and joining process are made.

Influence of the production process on the binding mechanism of clinched aluminum steel mixed compounds - Kalich, J.; Füssel, U. (Journal of Manufacturing and Materials Processing)
The multi-material design and the adaptability of a modern process chain require joining connections with specifically adjustable mechanical, thermal, chemical, or electrical properties. Previous considerations primarily focused on the mechanical properties. The multitude of possible combinations of requirements, materials, and component- and joining-geometry makes an empirical determination of these joining properties for the clinching process impossible. Based on the established and empirical procedure, there is currently no model that takes into account all questions of joinability—i.e., the materials (suitability for joining), design (security of joining), and production (joining possibility)—that allows a calculation of the properties that can be achieved. It is therefore necessary to describe the physical properties of the joint as a function of the three binding mechanisms—form closure, force closure, and material closure—in relation to the application. This approach illustrates the relationships along the causal chain “joint requirement-binding mechanism-joining parameters” and improves the adaptability of the mechanical joining technology. Geometrical properties of clinch connections of the combination of aluminum and steel are compared in a metallographic cross-section. The mechanical stress state of the rotationally symmetrical clinch points is qualified with a torsion test and by measuring the electrical resistance in the base material, in the clinch joint, and during the production cycle (after clinching, before precipitation hardening and after precipitation hardening).

Stochastic local FEM for computational homogenization of heterogeneous materials exhibiting large plastic deformations - Pivovarov, D.; Mergheim, J.; Willner, K.; Steinmann, P. (Computational Mechanics)
Computational homogenization is a powerful tool allowing to obtain homogenized properties of materials on the macroscale from simulations of the underlying microstructure. The response of the microstructure is, however, strongly affected by variations in the microstructure geometry. In particular, we consider heterogeneous materials with randomly distributed non-overlapping inclusions, which radii are also random. In this work we extend the earlier proposed non-deterministic computational homogenization framework to plastic materials, thereby increasing the model versatility and overall realism. We apply novel soft periodic boundary conditions and estimate their effect in case of non-periodic material microstructures. We study macroscopic plasticity signatures like the macroscopic von-Mises stress and make useful conclusions for further constitutive modeling. Simulations demonstrate the effect of the novel boundary conditions, which significantly differ from the standard periodic boundary conditions, and the large influence of parameter variations and hence the importance of the stochastic modeling.

Anisotropic plasticity‐damage material model for sheet metal — Regularised single surface formulation - Friedlein, J.; Mergheim, J.; Steinmann, P. (PAMM)
Sheet metal forming as well as mechanical joining demand increasingly accurate and efficient material modelling to capture large deformations, the inherent sheet orthotropy and even process-induced damage, which is expected to be influential. To account for large strains the additive logarithmic strain space is utilised that enables a straightforward incorporation of plastic anisotropy, herein modelled by a Hill48 yield function. A gradient-enhancement is used to equip the ductile damage model with an internal length scale curing the damage-induced localisation. An affine combination of the local and non-local softening variable is derived enabling a more efficient single surface formulation for the regularised plasticity-damage material model.

Further development of a numerical method for analyzing the load capacity of clinched joints in versatile process chains - Bielak, Christian Roman; Böhnke, Max; Bobbert, Mathias; Meschut, Gerson

Data-driven analysis of cold-formed pin structure characteristics in the context of versatile joining processes - Römisch, D.; Zirngibl, C.; Schleich, B.; Wartzack, S.; Merklein, M. (IOP Conference Series: Materials Science and Engineering)
Due to increasingly strict emission targets and regulatory requirements, especially for companies in the transport industry, the demand for multi-material-systems is continuously rising in order to lower energy consumption. In this context, mechanical joining processes offer an environmentally friendly and flexible alternative to established joining methods, especially in the field of lightweight design. For example, cold-formed cylindrical pin structures show high potentials in joining multi-material-systems without auxiliary elements. The pin structures are joined either by pressing them directly into the joining partner or by caulking with a pre-punched part. However, to evaluate the strength of the joint and to ensure the joining reliability for versatile processes, such as changing joining partners or batch variations, engineering designers currently have only limited design principles available compared to thermal joining processes. Consequently, the design of an optimal pin joint requires cost- and time-intensive experimental investigations and adjustments to design or process parameters. As a solution, data-driven methods offer procedures for structuring data and identifying dependencies between varying process parameters and resulting pin structure characteristics. Motivated by this, the paper presents an approach for the data-driven analysis of cold-formed pin structures and offers a deeper understanding of how versatile processes affect the pin characteristics. Therefore, the application of an intelligent design of experiment in combination with several machine learning methods enable the setup of a best-fitting meta-model. Resulting, the determination of a mathematical model provides the opportunity to accurately estimate the pin height considering only relevant geometrical and process parameters with a prediction quality of 95 %.

Numerical and experimental investigation of the transmission moment of clinching points - Steinfelder, C.; Kalich, J.; Brosius, A.; Füssel, U. (IOP Conference Series: Materials Science and Engineering)
In clinching, the combinations of requirements, materials, component dimensions and tools influence the resulting joint geometry and the resulting bonding mechanisms. These in turn affect the property profile of the joint. For example, it is possible to use different tools to flexibly adapt clinching points to the respective required load regime. Clinching points dimensioned in this way can be geometrically similar, but have different mechanical stress states, which leads to different properties in terms of load-bearing behavior. Within the scope of this work, the clinching process with different tools in optimal and compromise design and its effect on the force and form-closure component, is investigated in a torsion test of the clinched connection. Clinched steel sheets with two thicknesses and joining directions are analyzed. Virtual experiments are carried out using finite element analyses (FEA) of the joining process and are followed by a springback simulation. Subsequently, the surface pressure between the two joining partners in the clinching points is calculated on the basis of the results from the FEA and the transmittable moment of the connection, as an indicator for the force-closure component, is determined. Finally, the experimental and simulated data are compared and discussed.

Fiber Orientation Mechanism of Continuous Fiber Reinforced Thermoplastics Hybrid Parts Joined with Metallic Pins - Popp, J.; Kleffel, T.; Römisch, D.; Papke, T.; Merklein, M.; Drummer, D. (Applied Composite Materials)
Continuous Fiber Reinforced Thermoplastic (CFRT) hybrid parts offer interesting possibilities for lightweight application, which can exceed the capabilities of mono material metal or CFRT parts. In this case, the joining technology oftentimes is the limiting factor. This study investigates a joining operation with metal pin structures which are additively manufactured via powder bed fusion featuring different diameters and tip geometries, which are inserted into the locally infrared heated CFRT part. The resulting fiber rearrangement is assessed using transmitted light microscopy, confocal laser scanning microscopy as well as micro-computer-tomography. It could be shown that for all assessed pin variants a similar distinct fiber displacement can be seen and that the pin diameter has a significant effect on the resulting fiber orientation with smaller pin diameters being advantageous because of gentle fiber displacement and reduced undulation. The tip geometry has only minor effect on the fiber orientation. Especially in the X/Y plane no systematic influence of the tip geometry on the fiber displacement could be observed. Based on the gained insights a three-stage model of the fiber orientation processes is proposed.

Clinching of Thermoplastic Composites and Metals—A Comparison of Three Novel Joining Technologies - Gröger, B.; Troschitz, J.; Vorderbrüggen, J.; Vogel, C.; Kupfer, R.; Meschut, G.; Gude, M. (Materials)
Clinching continuous fibre reinforced thermoplastic composites and metals is challenging due to the low ductility of the composite material. Therefore, a number of novel clinching technologies has been developed specifically for these material combinations. A systematic overview of these advanced clinching methods is given in the present paper. With a focus on process design, three selected clinching methods suitable for different joining tasks are described in detail. The clinching processes including equipment and tools, observed process phenomena and the resultant material structure are compared. Process phenomena during joining are explained in general and compared using computed tomography and micrograph images for each process. In addition the load bearing behaviour and the corresponding failure mechanisms are investigated by means of single-lap shear tests. Finally, the new joining technologies are discussed regarding application relevant criteria.